Proportional operation review of irrigation schemes in Kastamonu area located in northern Turkey (International Journal of Irrigation and Water Management, 2014)
Performance analysis of six irrigation schemes in Kastamonu area located in northern Turkey were assessed using comparative performance indicators between the years 2008 and 2012. Performance indicators used for the analysis included relative water supply, financial performance as cost recovery ratio, maintenance expenditure to revenue ratio, operational cost per unit area, total cost per personnel employed on water delivery, revenue collection performance and service area per personnel. Additionally, production performance of the schemes were evaluated in terms of output per unit command area, output per unit irrigated area, output per unit irrigation supply and output per unit consumed-water. The results of the analysis indicated that all irrigation schemes except Asar had enough performance for the relative water supply ratios. Furthermore, cost recovery ratio and revenue collection performance was not satisfactory. On the other hand, maintenance expenditure to revenue, operational cost per unit area, total cost per person employed on water delivery and service area per personnel had performed well in most of schemes during the study years. Output per unit command area, output per unit irrigated area, output per unit irrigation supply and output per unit consumedwater were performed well for all schemes in the investigation year.